The Date of P. Alex. Inv. 622, Page 28. A Papyrus from Herakleidou Meris in the Arsinoite Nome - Ismail, Hanan M. I. (Hyperboreus, 2023)
This paper endeavors to determine the proper date of P. Alex. inv. 622, page 28, a papyrus from the holding of Alexandria’s Greco-Roman Museum. In “Catalogue des Monuments exposés au Musée Gréco-Romain d’Alexandrie” (1901) it was registered as a papyrus from the Byzantine period. In the publication of 1964 it was undated, and in online databases it is dated diﬀerently. As a result, this document has not properly been taken into account in scholarly research. The study of the document from a historical perspective (onomastic and prosopographic analysis of the name Μάρκος Ἀντώνιος Ἀ̣πολλινάριος and considerations on the toponym πεδίον Ψεναρψεννήσεως) allows to date the papyrus from 50 to 200 AD and draw attention to its potential historic value.